(untitled) (International Journal of Innovative Technologies in Economy, 2020)
This paper aims to make an empirical analysis of the impact of international competitiveness on China and Mongolia’s transportation service trade. First, calculating the RCA competitiveness index, China, Mongolia and some developed countries are compared and analyzed, and then an empirical analysis of the main factors influencing China and Mongolia transportation service trade is conducted, and it is concluded that the port freight export volume increased by 1%, China-Mongolia port freight export volume increased by 0.798%. When the opening of the transportation service industry in China and Mongolia increased by 1%, the export value of the transportation service trade increased by 1.232%. Therefore, the port exports of the two countries have a positive impact on the international competitiveness of the transportation service trade and the opening degree of the transportation service industry in China and Mongolia.